2′-O-Methyl molecular beacon: a promising molecular tool that permits elimination of sticky-end pairing and improvement of detection sensitivity. Issue 68 (14th November 2020) - Gao, Jiafeng; Li, Yang; Li, Wenqin; Zeng, Chaofei; Xi, Fengna; Huang, Jiahao; Cui, Liang
Abstract : A novel fluorescence sensor is reported based on the employment of an intriguing 2′- O -methyl molecular beacon (MB) and DNase I, the coupled use of which is responsible for both the elimination of the sticky-end pairing effect and signal amplification capability. Abstract : An innovative 2′- O -methyl molecular beacon (MB) has been designed and prepared with improved thermal stability and unique nuclease resistance. The employment of 2′- O -methyl MBs helps efficiently suppress the background signal, while DNase I is responsible for the signal amplification and elimination of sticky-end pairing. The coupled use of 2′- O -methyl MBs and DNase I makes it possible to develop an enzyme-aided strategy for amplified detection of DNA targets in a sensitive and specific fashion. The analysis requires only mix-and-measure steps that can be accomplished within half an hour. The detection sensitivity is theoretically determined as 27.4 pM, which is nearly 200-fold better than that of the classic MB-based assay. This proposed sensing system also shows desired selectivity. All these features are of great importance for the design and application of MBs in biological, chemical, and biomedical fields.